PERAN HIDROKSIAPATIT SEBAGAI MATERIAL BONE GRAFT DALAM MENSTIMULASI KEPADATAN KOLAGEN TIPE L PADA PROSES PENYEMBUHAN TULANG - Ardhiyanto, Hengky Bowo (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Bone has natural repair mechanism, but there are some critical sized defects which the tissues will not regenerate themselves and need clinical repair. Hydroxyapatite, as a popular bone substitute material, can be synthesized from nature. Recently, ceramic materials like hydroxyapatite have received much attention from both researchers and surgeons because of their biocompatibility, good mechanical properties and easy handling. Moreover, many have shown bio-absorbable properties compatible with those of various surgical applications permitting the complete bone regeneration and avoiding further interventions to remove the device. The conclusion is hydroxyapatite was affects for density of type l collagen in bone healing process.